Who Are the Experts, and What Have They Done for Us Lately?. - Stytz, M.R (IEEE Security and privacy : building confidence in a networked world)
Gaining the recognition for the security and privacy field as an assemblage of experts requires more than a simple assertion of expertise and a declaration of standards. We must be able to objectively assess our own performance, individually and as a whole, and determine if we are, as a field, improving computer security.